PERHITUNGAN KERUGIAN ENERGI PADA PENYULANG TAMBAK LOROK-03 SEBAGAI SALAH SATU PILOT PROJECT PROGRAM REVASS (REVENUE ASSURANCE) DALAM PROGRAM REKONSILIASI ENERGI PT. PLN (PERSERO) AREA SEMARANG - Putranti, Ruri Diana; Setiono, Iman (Vocational School Diponegoro University, 2014)
Ruri Diana Putranti, Iman Setiono, in paper calculation of energy losses of Tambak Lorok - 03 feeder as one of the pilot project program REVASS (revenue assurance) in energy reconciliation program of PT . PLN (persero) semarang area explain that in an electric power system there is a factor called the loss factor or energy depletion . This shrinkage can be found in various places on the electricity network , from generation, transmission and distribution of both to consumers . The release of energy or commonly referred to as shrinkage , the harm to the company for commercial and service in large and small quantities . Pond feeder Lorok - 03 is one of the feeders are thought to have a large enough energy depletion . This feeder is in the working area of ​​PT . PLN Rayon East Semarang and is a feeder into the pilot established REVASS ( Revenue Assurance ) PT . PLN Semarang area . Based on mathematical calculations that have been carried out in February 2013 the amount of power loss in the feeder is 2,316,319 KWH , while in the month of March 2013 is 4,765,637 KWH and in April 2013 amounted to 18,809,238 KWH . The amount of power loss raises the average monthly percentage losses in the feeder that is between 10-20 % . This of course lead to a loss for the company , especially on the commercial side that is the size of the company to the customer's receivables . Therefore , a program in which reconciliation is REVASS this project , is one attempt to get the suitability amount of energy from the power sent to the power received at the customer . Keywords : Electric Power System , Network Distribution , Energy Losses , Reconciliation of Energy